Isotopic evidence for volatile loss driven by South Pole-Aitken basin–forming impact - Heng-Ci Tian; Chi Zhang; Wen-Jun Li; Dingshuai Xue; Jing Wang; Wei Yang; Yan-Hong Liu; Yangting Lin; Xian-Hua Li; Fu-Yuan Wu (Proceedings of the National Academy of Sciences, 2026)
Recent studies suggest that the lunar farside experienced a magma ocean evolution similar to that of the nearside. Thus, the nearside-farside dichotomy, such as volcanism and crustal thickness, is likely related to the South Pole-Aitken (SPA) basin–forming impact. Although the noritic clasts found in Chang’e-6 (CE6) samples may originate from crustal remelting induced by the SPA impact, how (and whether) the lunar mantle was modified by this event remains unclear. Here, we present the first high-precision iron (Fe) and potassium (K) isotopic measurements of CE6 low-Ti basalts, revealing higher δ 56 Fe (0.13 to 0.21‰) and δ 41 K (0 to 0.09‰) in these basalts compared to their Apollo and Chang’e-5 (CE5) counterparts (δ 56 Fe: 0 to 0.11‰; δ 41 K: −0.29 to −0.04‰). The heavy Fe and K isotopic signatures are unlikely to be derived from cosmogenic effects or the addition of impactor-derived materials. Instead, the heavy Fe isotopes can be explained by partial melting and fractional crystallization processes. For K isotopes, however, the data require that the mantle source beneath the SPA basin had a heavier K isotopic composition than that of the nearside mantle, most likely resulting from evaporation caused by the SPA-forming impact. Our results thus provide robust evidence for significant impact-induced modification of the lunar mantle and demonstrate that large-scale impacts may have played a key role in creating lunar asymmetry.